Banana Biscuits Increase The Size of Upper Arm Circumference (LILA) of Pregnant Women with Chronic Energy Deficiency (KEK) - rofi'ah, siti; munayarokh, munayarokh; Suhardjati, Suhardjati (Midwifery and Nursing Research, 2025)
Background: Good nutritional status is important in supporting the success of national development. Chronic Energy Deficiency in pregnant women can result in miscarriage, premature birth, birth defects, Low Birth Weight and fetal growth and development disorders. Providing Supplementary Food (PMT) made from local foods such as bananas can be an alternative to overcome KEK. Biscuits are processed dry cakes that have a long shelf life, are crispy, brittle and dry, brownish yellow or according to the ingredients and have a fragrant aroma with a savory and sweet taste.Methods: This study used a quasi-experimental design with One-Group Pre Test-Post Test Design. Data analysis used the Wilcoxon test.Results: The size of the LILA of KEK pregnant women before and after consuming banana kepok biscuits was obtained an average of 22.73 cm and increased to 22.83 cm.Conclusion: Consumption of banana kepok biscuits has an effect on the size of the LILA of KEK pregnant women. Pregnant women are expected to increase their nutritional intake by consuming banana kepok biscuits to prevent and overcome KEK